Job Training Supports Better Individual Performance in Msmes through Job Satisfaction - Fery Riyanto; Fendy Suhariadi; Rini Sugiarti (Budapest International Research and Critics University, 2022)
The purpose of the study was to determine the effect of the work environment, job satisfaction, and training on individual performance in micro, small and medium enterprises (MSMEs) in Kelet village, Jepara district. The population in this study were 105 MSME actors in Kelet village consisting of food production MSMEs and service MSMEs. The sample is 105 employees of SMEs in Kelet village using the census sampling technique. The research technique used is a quantitative research technique using a structural equation model (SEM) with the AMOS 26 program. The results show 1) The work environment has a significant effect on job satisfaction for MSME actors in Kelet village, 2) Job training has no effect on job satisfaction for MSME actors. Kelet village, 3) Job satisfaction has a significant effect on the individual performance of MSMEs in Kelet village.